Longitudinal research and early years policy development in the UK - Melhuish, E (SpringerOpen, 2016)
Interest in early years issues such as early childhood education and care (ECEC) and early intervention has increased in recent decades internationally. Partly this reflects interest in facilitating the social and educational development of children, both for deprived children and the general population, and partly interest in increasing parental, particularly maternal, employment. Concern for such issues has led to substantial policy change in the UK in recent decades. For the general population, prior to 1998 there was no statutory obligation for the state to provide any early childhood services for children under the statutory school age of 5 years. However, there were provisions for ‘at risk’ children, as well as in some nursery education for 3- and 4-year olds, typically in more disadvantaged areas, but availability was haphazard around the country. Research evidence and social and political factors have resulted in radical change to the whole early years services system in the UK. The findings of two longitudinal research studies, the national evaluation of Sure Start and the effective provision of pre-school education projects were important factors in policy change and this paper discusses how the interplay of research and policy occurred. Initially changes were introduced by the Labour government, but more recent policy changes have been introduced by the Conservative government. The need for state involvement in early years services has become accepted by all political parties. There is substantially greater government investment in the early years, so that government-funded ECEC is now part of the infrastructure supporting family life for the whole population. This article discusses how research evidence has contributed to the substantial policy change in the last two decades.